2013
DOI: 10.1016/j.drugalcdep.2012.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine does not alter cocaine use in cocaine dependent individuals: A double blind randomized trial

Abstract: Background Cocaine abuse continues to be a significant public health problem associated with morbidity and mortality. To date, no pharmacotherapeutic approach has proven effective for treating cocaine use disorders. Preclinical and clinical evidence suggests that noradrenergic activity may play a role in mediating some effects of cocaine and may be a rational target for treatment. Methods This double blind, placebo-controlled randomized, parallel group, 12-week outpatient clinical trial enrolled cocaine depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The lack of therapeutic effects solely by ATO in the present study is not uncommon, as ATO has shown mixed effects on decreasing stimulant use (Levin et al, 2009; Walsh et al, 2013; Rush et al, 2011). A previous study indicated that ATO alone decreased reinstatement (Zlebnik and Carroll, 2015), but Broos and colleagues (2015) showed no effect on reinstatement if rats had received extinction training.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The lack of therapeutic effects solely by ATO in the present study is not uncommon, as ATO has shown mixed effects on decreasing stimulant use (Levin et al, 2009; Walsh et al, 2013; Rush et al, 2011). A previous study indicated that ATO alone decreased reinstatement (Zlebnik and Carroll, 2015), but Broos and colleagues (2015) showed no effect on reinstatement if rats had received extinction training.…”
Section: Discussionmentioning
confidence: 62%
“…In humans, ATO decreased both physiological (e.g., blood pressure increases) and subjective (e.g., pleasurable ratings) responses to d-amphetamine (Sofouglu et al, 2009). However, in some studies, no effects of ATO on stimulant use have been found (Levin et al, 2009; Walsh et al, 2013; Rush et al, 2011). …”
Section: Introductionmentioning
confidence: 98%
“…Using ATO, studies have demonstrated reduced impulsivity across a range of behavioral tasks such as the 5-choice serial reaction time (Baarendse and Vanderschuren 2012, Robinson et al 2008), stop-signal reaction time (Robinson et al 2008), and delay-discounting (Bizot et al 2011, Robinson et al 2008) tasks (but see Baarendse & Vanderschuren, 2012, Broos et al 2012, Sun et al 2012). Regarding atomoxetine’s effects on stimulant addiction, some clinical investigations have found no therapeutic effect on cocaine use (Levin et al 2009, Walsh et al 2013) and the subjective effects of methamphetamine (Rush et al 2011), while others found reduced physiological and subjective effects of d-amphetamine (Sofuoglu et al 2009), significant attenuation of alcohol cravings (Wilens et al 2011), longer abstinence from alcohol use (Benegal et al 2013), and fewer days of heavy alcohol drinking (Wilens et al 2008). Similarly equivocal findings were demonstrated in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Although further work is needed to clarify species-related differences in the neurochemical and behavioral effects of DβH inhibition, it seems evident that modulating NE neuronal activity can directly influence the behavioral effects of cocaine (see also Kohut et al 2013). Moreover, increased or decreased noradrenergic activity alone is not associated with reinforcement, consistent with the low abuse liability of directly- or indirectly-acting NE-related drugs (Wee and Woolverton 2004; Wee et al 2006; Walsh et al 2013) and supporting the further investigation of candidate medications with prominent noradrenergic actions for cocaine use disorder.…”
Section: Introductionmentioning
confidence: 57%